THE FIRST YEAR OF THE ABDOMINAL AORTIC ANEURYSM MODULE OF THE PORTUGUESE NATIONAL REGISTRY OF VASCULAR PROCEDURES: IMPLEMENTATION, RESULTS E FUTURE DIRECTIONS - Bastos Goncalves, Frederico (2021)
Introduction: Clinical registries are fundamental tools to understand the reality and audit the treatment of abdominal aortic aneurysms (AAA). The Portuguese Society of Angiology and Vascular Surgery, promotor of the National Registry of Vascular Procedures (RNPV), has developed a AAA module that started in December 2019. The objective of this report is to present data of the first year of the AAA module from Portugal. Methods: The AAA module opened the possibility for voluntary registry since December 2019. After specific training of investigators, participating centres started registration in a progressive way throughout the year 2020. Registrations are performed in a specifically designed web-based tool. All degenerative AAA cases are registered (including juxta- or supra-renal), with or without iliac involvement. Thoraco-abdominal or isolated iliac aneurysms are excluded. Demographic, anatomical, risk factos, admission, treatment details and outcomes at 30-day/in-hospital are registered. One and five-year follow-up is optional. For the purpose of this report, only data referring to mode of admission and treatment, as well as perioperative mortality, are reported. Results: From December 2019 to December 2020, 350 patients were registred in the AAA module platform. Mean age is 74.3± 13.7 and 92.0% are male. Admission was elective in 76,9% of cases. Mean maximum aortic diameter was 63.9mm ± 19.9mm. Most patients presented with infra-renal aneurysms, in similar proportion for elective and urgent cases (79% vs 76%), p=0.16. Aortic diameter was the indication for repair in 59.4% of cases. Endovascular treatment (EVAR) was used in 68.9% of cases. In elective surgery, the proportion of EVAR was 75.7% and in urgent cases 45.7%, p < 0.01. In elective surgery, perioperative mortality was 3.3% (8 patients). For EVAR patients it was 2.8% and for open surgery 5.2%, p<0.01. In urgent surgery, perioperative mortality was 41.9%, lower for EVAR (20.0% vs. 61.6% for open surgery), p<0.01. Conclusion: In its first year, the AAA module of the RNPV produced important data that help understand the patterns of treatment of this pathology in Portugal. These data may help vascular centres in quality improvement by providing a benchmark for comparison.